Dactylitis in a patient with brucellosis - Ozgocmen, S; Ardicoglu, O; Ozcakar, L (Churchill Livingstone, 2001)
Dactylitis is an important feature of inflammatory arthritis and unusual complication of osteoarticular brucellosis. We report a case of dactylitis of the index finger in a female patient with brucellosis.
Keywords: Osteoarticular Complications; Spondylarthropathy